%a=[1,3,4,2,3,4,7,7,9,4]n=length(a);if(mod(n,2)==0)n=n;elsea(n+1)=0;n=n+1;endb1=0;fori=1:n/2if((a(2*i)-a(2*i-1))==1)if((mod(a(2*i-1),2)==0)&(mod(a(2*i),2)==1))b1=b1+1;endendend附录三sumc的源代码如下:functionb2=sumc(a)%a=[1,3,4,2,3,4,7,7,9,4]n=length(a);if(mod(n,2)==0)n=n;elsea(n+1)=0;n=n+1;endb2=0;fori=1:n/2if((a(2*i-1)-a(2*i))==1)if((mod(a(2*i-1),2)==1)&(mod(a(2*i),2)==0))b2=b2+1;endendend附录四sume的源代码如下:functiond1=sume(a)%a=[1,3,4,2,3,4,7,7,9,4]n=length(a);if(mod(n,2)==0)n=n;elsea(n+1)=0;n=n+1;endd1=0;fori=1:n/2if((a(2*i-1)-a(2*i))==1)if((mod(a(2*i-1),2)==0)&(mod(a(2*i),2)==1))d1=d1+1;endendend附录五sumf的源代码如下:functiond2=sumf(a)%a=[1,3,4,2,3,4,7,7,9,4]n=length(a);if(mod(n,2)==0)n=n;elsea(n+1)=0;n=n+1;endd2=0;fori=1:n/2if((a(2*i)-a(2*i-1))==1)if((mod(a(2*i-1),2)==1)&(mod(a(2*i),2)==0))d2=d2+1;endendend